STRATEGY OF RAUDHATUT THOLIBIN (ROBIN) ISLAMIC BOARDING SCHOOL SUMENEP IN FORTING RELIGIOUS RADICALISM IN THE 5.0 ERA - Alam, Suluh Mardika; Arifin, Zainal (JURNAL SETIA PANCASILA, 2023)
This research applies a qualitative research approach, aiming to delve into the phenomena experienced by subjects and generate descriptive information in the form of written or spoken words, pertaining to individuals and behaviors under observation. Therefore, this study can be classified as qualitative descriptive research. Pondok Pesantren Raudhatut Tholibin (ROBIN) in Sumenep integrates religious and scientific knowledge within its curriculum, while instilling values of tolerance, moderation, and balance in practicing faith. This Islamic boarding school also collaborates with other parties such as the community and other educational institutions,in order to expand its network and influence towards achieving peace and social harmony. Furthermore, this boarding school empowers its students to become agents of positive change in society by involving them in various social, humanitarian, and cultural activities. Through these strategies, the boarding school aims to anticipate and counteract the negative impacts of religious radicalism that could threaten the unity of the nation.